EFFECTS OF DIFFERENT GENERATIONS OF EMPLOYEES IN AN ORGANIZATION ON ORGANIZATIONAL COMMITMENT - Kuenwan, Krittiya; Tuamtong, Supatchai; Chaimongkol, Nartraphee (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2018)
Corporate executives, at present, should manage their work and responsibilities for each position, including benefits and welfare to meet the needs of their employees in each generation; Generation X, Generation Y and Generation Z. Organizational supports in terms of performance, duties, responsibilities and the environment of the workplace enhance the commitment of the employees, their passion and pride at work. Employees tend to devote themselves to make a good and effective performance without any idea of resignation and applying to other organizations. Therefore, executives should build the commitment in three generations: 1) Generation X employees need organizational support in order to be accepted, respected and honored by the organization. 2 ) Generation Y employees need organizational support in order to be recognized in the organization and opportunities to develop their skills relating to their corporate responsibilities. In addition, flexibility and balance between their working and private life hours, teamwork and beneficiary activities to society and the environment are also needed. 3)Generation Z require an opportunity to share their opinions. Works regarding design and creativity with online support system are needed. They prefer to be considered and assessed by the quality of work than seniority system. Moreover, the atmosphere at workplace and a good environment are necessary for them.